Familiarity-based stimulus generalization of conditioned suppression - Robinson, Jasper; Whitt, Emma; Jones, Peter M. (American Psychological Association, 2017)
We report that stimulus novelty/familiarity is able to modulate stimulus generalization and discuss the theoretical implications of novelty/familiarity coding. Rats in Skinner boxes received clicker → shock pairings before generalization testing to a tone. Before clicker training, different groups of rats received preexposure treatments designed to systematically modulate the clicker and the tone's novelty and familiarity. Rats whose preexposure matched novelty/familiarity (i.e., either both or neither clicker and tone were pre-exposed) showed enhanced suppression to the tone relative to rats whose preexposure mixed novelty/familiarity (i.e., only clicker or tone was pre-exposed). This was not the result of sensory preconditioning to clicker and tone.